Application of bacteriocin-producing Enterococcus faecium isolated from donkey milk, in the bio-control of Listeria monocytogenes in fresh whey cheese - Aspri, Maria; Field, Des; Cotter, Paul D.; Ross, Paul P.; Hill, Colin; Papademas, Photis (My University, 2017)
A total of 79 bacterial strains, previously isolated from donkey milk, were screened for their antimicrobial activity against several spoilage and foodborne pathogenic bacteria. Amongst them, 3 strains belonging to Enterococcus faecium displayed antimicrobial activity against Listeria monocytogenes, Staphylococcus aureus and Bacillus cereus. Mass spectrometry analysis demonstrated that all enterococci used in this study produced peptides with masses consistent with those for enterocins A and B. The cell-free supernatants of the identified bacteriocin-producing enterococci were equally active over a wide range of pH and heat treatments making them excellent candidates for potential applications in bio-preservation. Bacteriocins produced by these strains were tested for their capability to control post-processing contamination and growth of L. monocytogenes during refrigerated storage of artificially contaminated fresh whey cheese. One strain was considered bactericidal while the other two were classified as bacteriostatic.
Keywords: Bacilli; Bacillus cereus; Bacteria; Bacteriology